Distinguishing Pseudoprogression From True Early Progression in Isocitrate Dehydrogenase Wild-Type Glioblastoma by Interrogating Clinical, Radiological, and Molecular Features - Li, Mingxiao; Ren, Xiaohui; Dong, Gehong; Wang, Jincheng; Jiang, Haihui; Yang, Chuanwei; Zhao, Xuzhe; Zhu, Qinghui; Cui, Yong; Yu, Kefu; Lin, Song (Frontiers in Oncology, 2021)
Background: Pseudoprogression (PsP) mimicks true early progression (TeP) in conventional imaging which poses a diagnostic challenge in glioblastoma (GBM) patients who undergo standard concurrent chemoradiation (CCRT). This study aimed to investigate whether perioperative markers could distinguish and predict PsP from TeP in de novo IDH wild-type GBM patients. Methods: New or progressive gadolinium-enhancing lesions that emerged within 12 weeks after CCRT was defined as early progression. Lesions that remained stable or spontaneously regressed were classified as PsP, otherwise persistently enlarged as TeP. Clinical, radiological, and molecular information were collected for further analysis. Patients in the early progression subgroup were divided into derivation and validation sets (7:3, according to operation date). Results: Amongst 234 consecutive cases enrolled in this retrospective study, the incidence of PsP, TeP and neither patterns of progression (nP) were 26.1% (61/234), 37.6% (88/234) and 36.3% (85/234), respectively. In the early progression subgroup, univariate analysis demonstrated female (OR: 2.161, P=0.026), gross total removal (GTR) of the tumor (OR: 6.571, P<001), located in the frontal lobe (OR: 2.561, P=0.008), non-subventricular zone (SVZ) infringement (OR: 10.937, P<0.001), methylated MGMT promoter (mMGMTp) (OR: 9.737, P<0.001) were correlated with PsP, while GTR, non-SVZ infringement, and mMGMTp were further validated in multivariate analysis. Integrating quantitative MGMTp methylation levels from pyrosequencing, GTR and non-SVZ infringement showed the best discriminative ability in the random forest model for derivation and validation set (AUC: 0.937, 0.911, respectively). Furthermore, a nomogram could effectively evaluate the importance of those markers in developing PsP (C-index: 0.916) and had a well-fitted calibration curve. Conclusion: Integrating those clinical, radiological, and molecular features provided a novel and robust method to distinguish PsP from TeP, which was crucial for subsequent clinical decision-making, clinical trial enrollment, and prognostic assessment. By in-depth interrogation of perioperative markers, clinicians could distinguish PsP from TeP independent from advanced imaging.